2021
DOI: 10.21613/gorm.2021.1222
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Thymus Size in Pregnant Women with COVID-19 Infection

Abstract: OBJECTIVE: To determine the effect of SARS-CoV-2 infection on fetal thymus size by ultrasound. STUDY DESIGN: In this prospective study sonographic fetal thymus size was measured in pregnant women attending our hospital with confirmed SARS-CoV-2 infection by RT-PCR test and age-matched control group. The anteroposterior thymic and the intrathoracic mediastinal diameter was determined in the three-vessel view and their quotient, the thymic-thoracic ratio, was calculated. Results were compared between these two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Since the start of the pandemic, COVID‐19 still is a mystery regarding its fetal effects. To date, there is no evidence to prove vertical transmission, 9 but we know that the fetus is affected by the disease during both the acute and post‐infection periods 10–13 . We hypothesized that fetal cardiac morphology and functions might be influenced negatively in pregnant women after recovering from COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Since the start of the pandemic, COVID‐19 still is a mystery regarding its fetal effects. To date, there is no evidence to prove vertical transmission, 9 but we know that the fetus is affected by the disease during both the acute and post‐infection periods 10–13 . We hypothesized that fetal cardiac morphology and functions might be influenced negatively in pregnant women after recovering from COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…In the diabetic pregnant groups, the median value of the thymus diameter was 9 mm (5. [5][6][7][8][9][10][11][12][13][14][15], and the TT ratio was 0.28 AE 0.08. In healthy pregnant women, the median of thymus measurement was 10.1 mm (6.5-17), and the TT ratio was 0.31 AE 0.06.…”
Section: Discussionmentioning
confidence: 99%
“…As we applied in our study, the thymus can be established between the great vessels posteriorly and the chest wall anteriorly, fetal three vessels, and tracheal surface 3 . We defined the anteroposterior thymic and intrathoracic mediastinal diameter in the three‐vessel view, and the thymic‐thoracic ratio was calculated 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that this ratio remains constant in normal fetuses regardless of the gestational week 8 . It has been evaluated in high‐risk pregnancies and aneuploidies in various studies 10–14 . Thymic hypoplasia or aplasia, which was first found to be associated with fetuses with 22q11.2 chromosome deletion and cardiac defects, continues to be of interest 10 .…”
Section: Introductionmentioning
confidence: 99%